(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Kendarini N, Aisyah SI, Maharijaya A, Sobir. 2022. Photoperiod effect on vegetative growth and bulbing initiation of four garlic genotypes. Biodiversitas 23: 4716-4723. The main factors influencing garlic growth and development were genetics, photoperiod, and temperature. Low temperature and short photoperiod were required for initial growth, followed by a long photoperiod and high temperature for bulbing and bolting. The study was conducted to evaluate the response of garlic genotypes to photoperiod on the vegetative growth and bulbing initiation, and physiological traits (C/N ratio, GA, and total chlorophyll content). Four garlic genotypes used in this experiment consisted of two Chinese garlic genotypes (hardneck and softneck) and two local garlic cultivars (Sangga Sembalun and Tawangmangu Baru). The garlic plants were subjected to the treatment of short photoperiod (control) and long photoperiod (night break and extension methods). The results showed that the Chinese hardneck and softneck had plant vegetative growth with a higher vigor than Sangga Sembalun and Tawangmangu Baru in all photoperiod treatments. Sangga Sembalun and Tawangmangu Baru had bulbing index below 0.3 in all photoperiods. The Chinese hardneck and softneck genotypes had bulbing index greater than 0.5 in all photoperiod treatments, except the hardneck in the night break treatment. The bulbing initiation in Chinese garlic genotypes was delayed in long photoperiod treatments. High temperature during the experiment affected bulbing initiation in long photoperiod treatment. The garlic genotypes had different responses to photoperiod treatments in C/N ratio, GA, and total chlorophyll content. The vegetative growth increased under extension treatment, and night break accelerated bulb formation. Long photoperiod increased C content and C/N ratio in the leaves while it decreased N content and photosynthetic pigment content. The late maturity time (Chinese hardneck and Chinese softneck) depended on long photoperiods for the bulbing formation. In contrast, local garlic cultivars with the early and mid-season types (Sangga Sembalun and Tawangmangu Baru) were insensitive to photoperiod.